Comparison Between Tafsir Al-Zamakhsyari And Al-Qurtubi Regarding The Interpretation Of Verse 59 Of Surah Al-Ahzāb - Ikmal Adnan; Khairulnazrin Nasir; Rahim Kamarul Zaman; Ahmad Asraff Ismail (Rabbanica: Journal of Revealed Knowledge)
The history of interpretation of the Qur'an has started since the time of the Prophet SAW. The process of its development happened so rapidly that there were many famous scholars who produced works in the interpretation of the Qur'an. Along with its progress, there are two forms of interpretation of the Qur'an, namely Tafsīr bi al-Ma'thūr and Tafsīr bi al-Ra'yi. There are many figures who use the method of Tafsīr bi al-Ra'yi, among them is the work of Abu Qasim Mahmud bin Umar al-Zamakhsyari (d. 538H) known as Tafsir al-Kasysyāf and the work of Abu Abdullah Muhammad bin Ahmad bin Abi Bakr al -Qurtubi (d. 671H) known as Tafsir al-Qurtubi. Therefore, this article aims to conduct a comparative study between the interpretation methods by al-Zamakhsyari and al-Qurtubi, especially regarding verse 59 of surah al-Ahzāb. This study uses a qualitative approach through the literature review theme. Data collection is from documentation sources such as thesis, dissertations and scholarly articles. While the form of data analysis applied is descriptive and comparative. The results of the analysis show that the methods used by al-Zamakhsyari and al-Qurtubi are different in the form of arrangement, discussion topics and explanations. In conclusion, the study related to the comparison of interpretation methods among scholars of interpretation needs to be expanded to identify the best method in understanding the holy verses of the Quran.